Korelasi antara Derajat Deviasi Septum Nasi dengan Aerasi Telinga Tengah dan Rongga Mastoid menggunakan Modalitas CT Scan - Andono, Rio; Latief, Nikmatia; Idris, Nurlaily (Jurnal Biomedik : JBM, 2021)
Abstract: Nasal septum deviation can affect the middle ear aeration-mastoid pneumatization system. The aim of this study was to analyze the correlation between the degree of nasal septum deviation with middle ear aeration and mastoid cavity using CT scan. Conducted retrospectively on nasal septum deviation patients who underwent a CT scan of paranasal sinuses at the central radiology department of  UNHAS, Makassar for the period of January 2018 to September 2020. Samples were as many as 48 patients aged >18 years who had diagnosed nasal septum deviation. The degree of nasal septum deviation is divided into mild (<9°), moderate (9-15°) and severe (>15°). The statistical method used was the Spearman correlation test. There was significant correlation between the degree of nasal septum deviation with ipsilateral tympanic membrane retraction with a p value 0,001 and ipsilateral mastoid pneumatization with a p value of 0.03 (<0,05). The results of this study indicate that there is significant correlation between the degree of nasal septum deviation with ipsilateral tympanic membrane retraction  and ipsilateral mastoid pneumatization. There is a correlation between moderate and severe nasal septum deviation with ipsilateral middle ear effusion, where the deviation degree of the nasal septum is getting increased, then there is a tendency for an increase in ipsilateral middle ear effusion compared to contralateral side.Keywords: Degree of nasal septum deviation, middle ear effusion, tympanic membrane retraction, mastoid pneumatization, CT Scan Abstrak: Deviasi septum nasi dapat mempengaruhi tekanan telinga tengah-sistem pneumatisasi mastoid. Tujuan penelitian ini adalah untuk menganalisis korelasi antara derajat deviasi septum nasi dengan aerasi telinga tengah dan rongga mastoid menggunakan modalitas CT-scan. Dilakukan secara retrospektif pada penderita deviasi septum nasi yang menjalani pemeriksaan CT-scan sinus paranasalis di instalasi radiologi sentral RS UNHAS, Makassar periode Januari 2018 sampai September 2020. Sampel sebanyak 48 orang dengan usia >18 tahun yang didiagnosis deviasi septum nasi. Derajat deviasi septum nasi dibagi menjadi ringan (<9°), sedang (9°-15°), dan berat (>15°) Metode statistik yang digunakan uji korelasi Spearman. Terdapat korelasi yang bermakna antara derajat deviasi septum nasi dengan retraksi membran timpani ipsilateral 0,001 dan pneumatisasi mastoid ipsilateral 0,03 (<0,05). Hasil penelitian ini menunjukkan terdapat korelasi yang bermakna antara derajat deviasi septum nasi dengan retraksi membran timpani ipsilateral dan pneumatisasi mastoid ipsilateral. Terdapat korelasi antara deviasi septum nasi derajat sedang dan berat dengan efusi telinga tengah ipsilateral, dimana semakin bertambah derajat deviasi septum nasi maka ada kecenderungan peningkatan efusi telinga tengah ipsilateral dibandingkan kontralateral.Kata kunci: Derajat deviasi septum nasi, efusi telinga tengah, retraksi membran timpani, pneumatisasi mastoid, CT Scan